Underlying Causes and Risk Factors of Chronic Renal Allograft Dysfunction Among Renal Transplant Recipients - Güven, Göksel; Yılmaz, Şeref Rahmi; Yıldırım, Tolga; Akı, Fazıl Tuncay; Erdem, Yunus (Acta Medica, 2021)
Objective: Dialysis or renal transplantation are the two treatment options for end-stage renal disease patients. Renal transplantation from an appropriate donor increases survival and quality of life compared to treatment with dialysis. Recent advances in immunosuppressive therapy have significantly improved the success in 1-year graft survival. However, the long-term graft survival remains the same. Therefore, we aimed to determine the underlying causes and risk factors of chronic allograft dysfunction in renal transplant recipients. Materials and Methods: From 2000 to 2012, all consecutive renal transplant recipients followed in our tertiary referral center who underwent renal biopsy due to an increase in serum creatinine level were enrolled. Etiologies of chronic allograft dysfunction were assessed according to pathologic results of renal biopsy specimens and laboratory findings. The immunological and non-immunological risk factors of chronic allograft dysfunction were screened and recorded retrospectively. Results: Eighty (80) renal transplant recipients with a mean age of 38±10 years were included in the study. Delayed graft function (p=0.007), history of acute rejection (p<0.001), positive panel reactive antibody (p=0.033) (Class I (p=0.013), Class II (p=0.006)), positive donor specific antibodies (p=0.001), number of recurrent acute rejections (p<0.001), number of human leukocyte antigens mismatches (p=0.051), cold ischemia time (p=0.001) were found to be risk factors for chronic allograft dysfunction. The donor specific antibodies positivity (p<0.001) and the panel reactive antibody positivity (Class I (p=0.003), Class II (p=0.001)) were significantly higher in patients with antibody mediated rejection than patients without antibody mediated rejection (p=0.002). Conclusion: Delayed graft function, presence and the number of acute rejections, increased cold ischemia time, panel reactive antibody positivity, donor specific antibodies positivity, and the number of human leukocyte antigens mismatches were risk factors for chronic allograft dysfunction.